2018
DOI: 10.4055/cios.2018.10.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fat Infiltration in Cervical Extensor Muscles on Cervical Lordosis and Neck Pain: A Cross-Sectional Study

Abstract: BackgroundWeakness of cervical extensor muscles causes loss of cervical lordosis, which could also cause neck pain. The aim of this study was to investigate the impact of fat infiltration in cervical extensor muscles on cervical lordosis and neck pain.MethodsFifty-six patients who suffered from neck pain were included in this study. Fat infiltration in cervical extensor muscles was measured at each level of C2–3 and C6–7 using axial magnetic resonance imaging. The visual analogue scale (VAS), 12-Item Short For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…25 Our finding that neck disability could be associated with fatty infiltration of deep posterior paraspinal muscles according to the severity of OPLL, is consistent with these previous results. 25,41 Clinical manifestations, paraspinal muscle degeneration, and OPLL morphology may have a complex interaction with each other and lead to a cycle of repeated neck-associated clinical problems. A better understanding of the mechanisms underlying the development of clinical manifestations owing to paraspinal muscle degeneration could contribute toward better clinical management of patients with cervical OPLL.…”
Section: Discussionsupporting
confidence: 93%
“…25 Our finding that neck disability could be associated with fatty infiltration of deep posterior paraspinal muscles according to the severity of OPLL, is consistent with these previous results. 25,41 Clinical manifestations, paraspinal muscle degeneration, and OPLL morphology may have a complex interaction with each other and lead to a cycle of repeated neck-associated clinical problems. A better understanding of the mechanisms underlying the development of clinical manifestations owing to paraspinal muscle degeneration could contribute toward better clinical management of patients with cervical OPLL.…”
Section: Discussionsupporting
confidence: 93%
“…If the load balance and lordosis are not restored, the altered cervical curvature will eventually progress to kyphosis. [3233]…”
Section: Discussionmentioning
confidence: 99%
“…[1,13] The change of cervical lordotic curve was usually found by cervical spine images in clinic. [3,14] MRI has the superiority because of no radiation injury for human bodies compared with X-ray and CT. [1517] In this report we choose the frequently-used and good repeated methods to evaluate the cervical lordotic curvature including SVA, C2–C7 Cobb and T1S. [18,19] It has reported that C2–C7 SVA showed a positive correlation with NDI which was also certified in this study.…”
Section: Discussionmentioning
confidence: 55%